(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2010)
This prospective cohort study was conducted at the Combined Military Hospital, Dhaka during January 2003 to December 2005. Thirty patients with locally advanced stage III and stage IV squamous cell carcinoma of head and neck were treated with a short course palliative radiotherapy (30 Gray in 10 fractions over 2 weeks). All (100%) patients with pain and 90% of patients with dysphagia, dyspnoea and disturbed sleep had greater than 50% relief in symptoms after radiotherapy. Dysphonia and cough were satisfactorily relieved in more than 60% of cases. Eight of 30 lesions in this study had complete response; 14 lesions had a partial response; 4 lesions had no response; 2 lesions progressed under treatment. Response could not be assessed in two patients. Acute and late reactions were acceptable. After palliative radiotherapy 8(27%) patients were eligible for dose escalation and received further radiotherapy upto radical dose equivalent. It was concluded that short course palliative radiotherapy regimen evaluated is an effective treatment modality for sustained symptoms relief with good response rates and acceptable toxicity in locally advanced head-neck cancer. Key words: Palliation; radiotherapy; short course; head and neck cancer. DOI: 10.3329/jafmc.v6i1.5986 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.16-20